ANALYSIS OF REPRODUCTIVE AGE (PUS) COUPLES EDUCATION LEVEL BY CHOOSING OF CONTRACEPTIVE METHODS AT CEMPAKA PUTIH HEALTH CENTER - Johara Johara (Akademi Keperawatan RSPAD Gatot Soebroto, 2023)
Contraception is one of the efforts made by the government to reduce the growth rate of the population at high risk of unwanted abortions and pregnancies. 1.45% in the 1990-2000 period to 1.49% in the 2000-2010 period. Couples of Reproductive Age are expected to use contraceptive methods to reduce the population. The objectives of this study is to find out the analysis of reproductive age (PUS) couples educational level by choosing of contraseptive methods at Cempaka Putih Health Center. This study used a cross-sectional quantitative approach. Cross Sectional Measurement is a research design by measuring or observing at the same time. The result is found that most couples of reproductive age had a secondary education level of 19 respondents (63.3%), height of 9 respondents (30.0%), basic of 2 respondents (6.7%) and the choice of contraception for couples of reproductive age the most are modern, 25 respondents (83.3%) and as many as 5 respondents choose traditional (16.7%). The conclusion of this study is most of the respondents had the highest level of education (middle school and high school) and chose the most types of modern contraception (birth control pills, injections, implants, IUDs).